Numerical estimation of aluminium sheets heating caused by energy of lightning strokes - Struzewski, P. (Фізико-механічний інститут ім. Г.В. Карпенка НАН України, 2010)
The article deals with the description of usage of developed numerical model for metal sheets temperature fields estimation for determination of aluminium plates temperature increase lability after direct lightning hits. The author proved that in the case of logarithmic coordinates application, there is an approximation possibility of every of graphical interpretations of relationships between the maximum temperature increase of aluminum sheet point opposite to the site struck by lightning and the time of main discharge, by two rectilinear sections.